Identifikasi dan Morfometri Taman Setra di Kecamatan Ubud - SUGIANTHARA, ANAK AGUNG GEDE; SUDARSANA, ANAK AGUNG GEDE DALEM; SARWADANA, SANG MADE; LILA, I KOMANG ARTHAWA (Jurnal Arsitektur Lansekap; Vol.3, No.1, April 2017, 2017)
ABSTRACT Identification and Morphometry of Setra Park in Ubud District Ubud is one of eight district which is located in Gianyar regency. Ubud was selected as a study site because the distric has a cemetry park which is need to identify. The aim of the study was to identify cemetery park (setra park) in the district of Ubud. The method used was survey method with employing observation, interview, and literature study technique. Purposive random sampling was conducted with number of sample as much as 30 percent of total population of cemetery in Ubud. Overall, there were twelve cemetery selected namely Tunon, Demayu, Kengetan, Singakerta, Mawang, Mas, Peliatan, Padang Tegal, Dalem Puri Ubud, Petulu, Bentuyung, and Kedewataan respectively. Results showed that each cemetery park has a spatial pattern which is similar from one to others. The main part or utama mandala area of cemetery was Pura Prajapati. Likewise, in the middle part of cemetery or madya mandala area were pamuwunan and cemetery for children and adults. Whereas, in lower part of cemetery or nista mandala area there were landfills or remnants from ceremony, but there were some variations in the extent of their area and characteristic of each pakraman (local village institution). In terms of function, all cemetery parks has primary function as a place of burial and bodies cremation ceremony (pengabenan) as well as it additional function as a green open space, aesthetic and sicio-cultural-religious-magical functions. Similarly, each setra park has a similarity in term of layout and park element. Some variations were found in terms of plant species dominancy together with number and types of animals and plants found. Keywords: cemetery park, hard and soft elements, pakraman village, Ubud district